Effect of cerebrolysin on bladder function after spinal cord injury in female Wistar rats. (17th July 2019) - Abolhasanpour, Nasrin; Eidi, Akram; Hajebrahimi, Sakineh; Reyhani‐Rad, Siamak; Hashim, Hashim
Abstract : Objectives: To study the effect of cerebrolysin on bladder function after spinal cord injury using functional measurements in rats. Methods: A total of 60 female rats were enrolled in this study. After induction of complete transection at T9–T10 spinal vertebrae, cerebrolysin was injected intraperitoneally, and daily in three dosages until 7 days (1 week) and continued until 28 days (4 weeks) in three groups to show the impact of that on the bladder function. Urodynamic parameters were measured in the different groups. Results: Cerebrolysin injection in a dose of 1 mL/kg for 1 week showed a slight improvement in urodynamic parameters. However, infusion of 2.5 and 5 mL/kg cerebrolysin for 1 week caused an elevation in contractions and a decrease in compliance. In long‐term 2.5 mL/kg cerebrolysin injection, an improvement in compliance was observed, despite relative contractions. Furthermore, the bladder pressure pattern in the 2.5 mL/kg infused rats for 4 weeks was similar to the control group, but in the group receiving 5 mL/kg cerebrolysin for 4 weeks, reduced bladder contractions and function were observed. Conclusions: Our findings suggest that cerebrolysin might be able to inhibit the emergence of neurogenic detrusor overactivity in spinal cord injured female rats.